Лыз яг: повестьёс но веросъёс / Пётр Чернов - Чернов Петр Константинович (Удмуртия, 1991)
Экземпляры: ХР (20180523) / Инвентарный номер: 30325 / Цена: 1.60 / Сис.шифр: С(Удм) / Авт.знак: Ч 49 / ГРНТИ: 17.82.31 / ББК: С(Удм)